Perilaku Komunikasi Para Penggemar Korean Pop (Studi deskriptif Pada Masyarakat Rawasari) - Thomas Bambang Pamungkas; Lasmery RM Girsang; Ignatius Ricky Loyola (Communication Science Department - Faculty of Social and Political Sciences, Universitas Satya Negara Indonesia (USNI), 2023)
Korean Pop (K-Pop) has been endemic in Indonesia, especially in the Rawasari area, East Jakarta. Fans often share information, discuss K-Pop. Their communication behavior to Korea, of course, brings about a change in the culture of communication in Indonesia. This can be a problem for fans and the wider community. Based on the limitations that are focused on verbal communication carried out by KPOP fans in their daily behavior. This can be a problem for fans and the wider community. To find out the communication behavior of Kpop fans in social life, this study aims to find out the fanaticism of KPOP fans which is part of communication behavior. Qualitative research based on this constructivist paradigm found results from informants who live in the Rawasari area (East Jakarta) that Korean Pop (KPOP) is in demand by teenagers/younger generations in Jakarta.